Aging, Diet and Epigenetic Alterations to the DNA. - Tammen, Stephanie. (2017)
Abstract: DNA methylation is an epigenetic mark that can regulate gene transcription. Hydroxymethylcytosine is a newly discovered epigenetic mark that is the product of the oxidation of methylcytosine. This cytosine modification is important in the active removal of methylcytosine from the genome, and may regulate gene transcription. To analyze global percent hydroxymethylcytosine and changes in genome wide patterns of hydroxymethylcytosine two methods were successfully developed. Using DNA hydrolysis and LC/MS-MS global percent hydroxymethylcytosine can be quantified. The genomic location and relative abundance is measured using a hydroxymethylcytosine immunoprecipitation followed by an array (hmeDIP-Chip). Using these techniques, we have determined alterations in the abundance and location of hydroxymethylcytosine that are associated with aging and chronic alcohol consumption in the rodent liver. Aging is associated with significant changes in global hydroxymethylcytosine levels that may be diet dependent. Many site-specific alterations in genomic hydroxymethylation also occur in aging, including a decrease in hydroxymethylation in the promoter of the leptin receptor gene, as well as a decrease in transcription of that gene. Alcohol consumption was associated with a reduction in percent hydroxymethylcytosine in the livers of young mice only, with no significant changes in percent hydroxymethylcytosine in the old. Through microarray analysis, a region of DNA spanning a CpG island at the transcription start site of the glucocorticoid receptor was found to have increased hydroxymethylcytosine in the young mice fed alcohol relative to the young control group. Young mice fed alcohol also had an increase in transcription of the glucocorticoid receptor relative to the control. In patients with hepatocellular carcinoma due to moderate to high alcohol intakes, tumors have a significant decrease in percent hydroxymethylcytosine relative to adjacent normal tissue. From these genomic hydroxymethylcytosine patterns we speculate that a reduction in global hydroxymethylcytosine from chronic alcohol consumption may predispose a cell to carcinogenesis. In conclusion, both aging and alcohol consumption are associated with changes in global, genomic and site-specific changes in abundance of hydroxymethylcytosine, which may alter gene transcription and the risk for disease.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: Sang-Woon Choi.; Committee: Lynne Ausman, and Gregory Dolnikowski.; Keywords: Genetics, Nutrition, and Aging.